The Hermeneutics Methodology of Buddhadasa Bhikkhu - Atthasiddho, Pharkhruphaladsommai; Laphontan, Sanguan; Suanmafai, Phaitoon (Academic MCU Buriram Journal, 2021)
Methodology of understanding thoroughly in order to achieve intuition in core religious principles of Buddhism via Hermeneutics of Paul Ricoeur can be called Hermeneutics Methodology of Phenomenological Existentialism according to Buddhadasa Bhikkhu’s term: “Theory of Attaining Pure Intuition”. It practically helps to transform Human-hood as secularization of human language to language of beyond secularization in Lokutara status through Buddhadasa Bhikkhu’s examples of historical phenomenal understanding on various external discourses of humane evidences in paradigms of humankind and religious language, Manual of Humanity and Theater of the Soul for revealing universal language on Arts of Lokiya phenomena so that emptiness can be intuited clearly.